Photon-polarization-resolved linear Breit–Wheeler pair production in a laser-plasma system - Huai-Hang Song; Zheng-Ming Sheng (New Journal of Physics)
The linear Breit–Wheeler (LBW) process—the production of an electron–positron pair through the collision of two high-energy photons—can emerge as the dominant pair production mechanism in the ultraintense laser-plasma interaction for laser intensities below 10 ^23  W cm ^−2 . Here, we explore the role of γ photon polarization in LBW pair production for a 10 PW-class, linearly polarized laser interacting with a solid-density plasma. The motivation for this investigation lies in two main aspects: γ photons emitted via nonlinear Compton scattering are inherently linearly polarized, and the LBW process exhibits a distinct sensitivity to γ photon polarization. By leveraging particle-in-cell simulations that self-consistently incorporate photon-polarization-resolved LBW pair production, our results reveal that γ photon polarization leads to a 5% to 10% reduction in the total LBW positron yield. This suppression arises because the polarization directions of the colliding γ photons are primarily parallel, reducing the LBW cross section compared to the unpolarized case. The influence of γ photon polarization weakens as the laser intensity increases or the scale length of preplasmas at the front of the target increases.